A critical discourse analysis of the image of the Filipino woman in selected Philippine independent films by Filipino women independent film makers from 2004-2007 - Cosio, Ana Karina Avellana; Alfonso, Grace J. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2010)
This study focuses on how discourse constructs the image of Filipino women as they are represented in contemporary Philippine independent films by independent Filipino female filmmakers, specially between the years 2004 and 2007. Using the framework of Critical Discourse Analysis (CDA), this study examined the content and language of five full-length independent films that exhibited the discursive formations and the historical milieu in which the fiv film were produced and release. (CDA calls for a description of the historica; and cultural milieu of a particular discourse to provide the distinct worldview from which the discursive statements and formations emanate.) The contemporary independent films studied were produced and released within a period (2004-2007) characterized by developments in related studies on sexuality and the imaging of Filipino woman, reproductive health, the filing of bills on the morality of same-sex relations, pre-marital sex, abortion and the use of contraceptives by Filipino women, as well as studies on attitudes, perceptions and discursive sites on the issues mentioned above. As contemporary independent films which have themes on the imaging of woman, the narratives may still sometimes follow the structure and aural excesses of the melodramatic film but the films' texts do present new narratives, e.g. resistive and subversive.These images are contributive to the new imaging of the Filipino woman in the five contemporary independent films chosen for this study, and exemplify what sets them apart from Filipino mainstream cinema.
Thesis (M.A.-Media Studies)--University of the Philippines Diliman
Keywords: Women in the motion picture industry -- Philippines; Women -- Philippines